I, Ripper : a novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2015)
"The electrifying new thriller from New York Times bestseller Stephen Hunter takes you deep inside the mind of the most notorious serial killer of all time - Jack the Ripper"--Publisher.